Design and Psychometric Analysis of an Instrument Evaluating Basic Skills in Economics and Finance: A Contribution to the Consumer Education - Vargas Prieto, Mónica (Pontificia Universidad Javeriana, 2014)
In Colombia the lack of valid and reliable instruments that allow diagnostics and measurements that contribute to the definition of the content of programs in economic and financial education and their effectiveness in their objectives is evident. The purpose of this study was to design and conduct a psychometric analysis of an instrument to assess basic skills in financial and economic education in 410 university students older than 15. The instrument was developed according to the test plan and content validation was performed with 8 experts. The study was instrumental. Data were analyzed from the context of item response theory (IRT). Internal consistency was established by a Cronbach’s alpha value of 0.98. The values found for Outfit and Infit indicated good fit to the Rasch model. The results show that the test meets the psychometric requirements required for this type of instrument, becoming a useful tool for measuring basic skills in economics and finance.